EFFECT OF ADDITIONAL SODIUM TRIPOLYPHOSPHATE (STPP) CONCENTRATION ON PRODUCT PHYSICAL AND SENSORY CHARACTERISTICS WET NOODLES FROM LUMI-LUMI FISH (Harpodon numerous) FORTIFIED WITH RED BEET EXTRACT - Baida Lisma; Safrida; Sufyan Anwar; Sri Wahyuni Muhsin (PT. Radja Intercontinental Publishing, 2024)
Commercial noodles are generally made from wheat flour and eggs without adding fish, fruit, and vegetable extracts. Adding fish and red beet extract can increase the nutritional content and antioxidants in the resulting noodle product. Adding Sodium Tripolyphosphate (STPP) can improve the desired noodle texture, namely chewy and elastic. This study aims to identify the effect of the concentration of STPP addition on the physical characteristics and sensory acceptability of Lumi-lumi wet noodles fortified with red beet extract. The study used a single factorial Completely Randomized Design (RAL) with four different STTP concentration treatments (F1: 0%, F2: 0.50%, F3: 0.75%, F4: 1% STPP) with a ratio of wheat flour, Lumi-lumi fish, and red beet extract, namely 80%: 20%: 8%. The observations were physical quality tests, including rehydration, cooking time, cooking loss, and elasticity of noodle. 60 untrained panelists carried out sensory tests. There was a significant effect (P <0.05) of the addition of STPP concentration on the physical quality of noodles. Treatment F1 showed the best rehydration noodle and cooking time, 80.93% and 2.98 minutes, respectively. The best cooking loss and elasticity were obtained in F4, which were 19.93% and 27.08 mm. Sensory results significantly affected color and taste parameters (P<0.05). Aroma and texture had no significant effect (P>0.05). The highest color acceptance was obtained in F3, followed by F2, respectively 3.97 (like) and 3.80 (like). The best taste parameter was received in F2, 3.83 (like). The highest aroma was obtained in F3, followed by F2, respectively, 3.80 (like) and 3.75 (like). The highest texture assessment was in F4, followed by F3 and F2, respectively, namely, 3.55 (slightly chewy), 3.53 (slightly chewy), and 3.40 (slightly chewy). Based on the research results, to produce Lumi-lumi wet noodles with the desired physical and sensory acceptability, an STPP concentration of 0.50% is recommended.